Analysis of Financial Performance in Pharmaceutical Industry Sub-Sector Companies in Indonesia for the 2020 – 2022 Period - Sulistyani, Tri; Amalya, Neneng Tita (Transforma Jurnal Manajemen, 2024)
This research aims to determine the financial performance of pharmaceutical industry sub-sector companies in Indonesia for the 2020 - 2022 period if viewed from financial reports using solvency ratios and to determine the financial performance of pharmaceutical industry sub-sector companies in Indonesia for the 2020 - 2022 period if viewed from reports finance uses profitability ratios. The method used is descriptive and comparative methods. The population in this study were companies in the pharmaceutical industry sub-sector on the Indonesia Stock Exchange, while the samples were taken 3 from the existing pollution using a purposive sampling method and obtained by PT. Kalbe Farma Tbk (KLBF), PT. Indofarma Tbk (INAF) and PT. Tempo Scan Pasifik Tbk (TSPC). The results of this research are the financial performance of pharmaceutical industry sub-sector companies in Indonesia for the 2020 - 2022 period. If viewed from the financial reports using the solvency ratio, the Debt to Asset Ratio of PT. Kalbe Farma Tbk (KLBF) is in good condition. PT. Indofarma Tbk (INAF) is in bad condition and PT. Tempo Scan Pasifik Tbk (TSPC) is in good condition. Debt to Equity Ratio PT. Kalbe Farma Tbk (KLBF) is in good condition., PT. Indofarma Tbk (INAF) is in bad condition and PT. Tempo Scan Pasifik Tbk (TSPC) is in good condition. Meanwhile, the financial performance of pharmaceutical industry sub-sector companies in Indonesia for the 2020 - 2022 period, if viewed from the financial reports using profitability ratios, means that the Net Profit Margin of PT. Kalbe Farma Tbk (KLBF) is in poor condition. PT. Indofarma Tbk (INAF) is in very bad condition and PT. Tempo Scan Pasifik Tbk (TSPC) is in poor condition. Return On Assets PT. Kalbe Farma Tbk (KLBF) is in poor condition. PT. Indofarma Tbk (INAF) is in very bad condition and PT. Tempo Scan Pasifik Tbk (TSPC) is in poor condition. Return On Equity PT. Kalbe Farma Tbk (KLBF) is in poor condition. PT. Indofarma Tbk (INAF) is in very bad condition and PT. Tempo Scan Pasifik Tbk (TSPC) is in poor condition.